The Risk Mapping in the Czech Republic - Lenka BRUMAROVÁ; Jakub BRUMAR (Košická bezpečnostná revue, 2018)
The paper focuses on the issue of risk mapping in the conditions of the Czech Republic. This method is based on the risk mapping method developed by the Fire Rescue Service of the Czech Republic, which comes from the methodology recommended by the European Union. The aim of the paper is to characterize and determine selected starting points for risk mapping that are necessary for representation the risks on the map. It uses the interaction of different types of hazards with the vulnerability of the territory and the level of preparedness in that territory. Implementation of the risk mapping result for a given territorial unit is broad. Risk mapping is based primarily on the classification and quantification of risk in relation to the territory. It is a value-based result risk on the map.